Evaluation of proprioception after Bossu program in adolescent female volleyball players - Bivolarski, G.; Gencheva, N. (FIS communications in Physical Education, Sport and Recreation, 2016)
The aim of this study was to examine the effect of bossu program on developing proprioception. It was used the star excursion balance test because of its big reliability from 0.89 to 0.94. Twenty-four (N=24) female national volleyball team u19 players were participated in this study, but only eighteen (N18) based the inclusion criteria. It was used paired-simple t-test for analyze the results. Results indicated that there was a significant difference within the pre and post test results (p . 0.05). It was suggested that application of bossu program may improve significantly the proprioception and the postural control in young volleyball players.